Built‐In Electric Fields Dramatically Induce Enhancement of Osseointegration. (23rd October 2017) - Liu, Yun; Zhang, Xuehui; Cao, Cen; Zhang, Yuelin; Wei, Jinqi; Li, Yong jun; Liang, Weiwei; Hu, Zhewen; Zhang, Jinxing; Wei, Yan; Deng, Xuliang
Abstract: Rapid and effective osseointegration is a great challenge in clinical practice. Endogenous electronegative potentials spontaneously appear on bone defect sites and mediate healing. Thus, bone healing can potentially be stimulated using physiologically relevant electrical signals in implants. However, it is difficult to directly introduce physiologically relevant electric fields in bone tissue. In this study, built‐in electric fields are established between electropositive ferroelectric BiFeO3 (BFO) nanofilms and electronegative bone defect walls to trigger implant osseointegration and biological healing. Epitaxial growth technique is used to organize the crystal panel at an atomic scale, and ferroelectric polarization of BFO nanofilms matching the amplitude and direction of endogenous electric potentials on bone defect walls is achieved. In the presence of built‐in electric fields, implants with BFO nanofilms with downward polarization (BFO+) show rapid and superior osseointegration in the rat femur. The mechanism of this phenotypic osteogenic behavior is further studied by protein adsorption and stem cell behavior in different time points. BFO+ promotes protein adsorption and mesenchymal stem cell (MSC) attachment, spreading, and osteogenic differentiation. Custom‐designed PCR array examination shows sequentially initiated Ca 2+ signaling, cell adhesion and spreading, and PI3K‐AKT signaling in MSCs. The results of this study provide a novel strategy for the development of implant surface modification technology. Abstract : In this study, built‐in electric fields are established between electropositive BiFeO3 (BFO+) nanofilms and electronegative bone defect walls to trigger implant osseointegration. In vivo, BFO+ nanofilms show rapid and superior osseointegration in the rat femur. In vitro, BFO+ promotes protein adsorption and stem cell attachment, spreading, and osteogenic differentiation. The results of this study provide a novel strategy for implant surface modification technology.